Management of heart failure in Piedmont Region - Nicolò Montali (Monaldi Archives for Chest Disease, 2016)
emerging problem in industrialized countries: it continues to be diagnosed at high rates and has an decreased survival time, raising new problems, such as the need of an adequate medical service organization and resource expenditure. Aim of this analysis was a quantitative evaluation of diagnostic and therapeutic resource use for CHF in outpatient departments in Piedmont, Italy. Methods. We performed a cross-sectional observational study, based on a two-month data collection in 12 outpatient departments dedicated to congestive heart failure. Information was obtained on each patient using a specific anonymous data collection form. Results. We obtained and analyzed for the study 547 forms. Mean patient age was 66.1 years, mean ejection fraction was 36.6%. Coronary artery disease accounted for 34.6% of congestive heart failure cases, followed by idiopathic etiology (26.4%). Main comorbidities were diabetes (22.3%) and chronic obstructive pulmonary disease (17.7%). Sixty-nine% of patients received a medical treatment with angiotensin-converting enzyme (ACE) inhibitors, 72.6% with β-blockers, 48.8% with aldosterone antagonists. As far as diagnostic resource use during a six-month period preceeding observation, 46.8% of patients underwent echocardiographic examination, 9.9% Holter ECG, 6.0% coronary angiography. Therapy was more often increased in patients who underwent an instrumental evaluation during the preceeding six-month period. Conclusions. Data suggests that in Piedmont outpatients with chronic heart failure receive a high drug prescription level and a small number of instrumental evaluations, as suggested in main international guidelines.